2016
DOI: 10.3390/atoms4040030
|View full text |Cite
|
Sign up to set email alerts
|

Cross Sections and Rate Coefficients for Vibrational Excitation of HeH+ Molecule by Electron Impact

Abstract: Abstract:Cross sections and thermally-averaged rate coefficients for vibration (de-)excitation of HeH + by an electron impact are computed using a theoretical approach that combines the multi-channel quantum defect theory and the UK R-matrix code. Fitting formulas with a few numerical parameters are derived for the obtained rate coefficients. The interval of applicability of the formulas is from 40 to 10,000 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…In a previous study [19] (hereafter referred to as paper I), we reported cross sections and rate coefficients for vibrational excitation for transitions between the five lowest vibrational levels. In a further study [20] (hereafter referred to as paper II), we presented similar data for rotational transitions in collisions of 4 HeH + with electrons.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study [19] (hereafter referred to as paper I), we reported cross sections and rate coefficients for vibrational excitation for transitions between the five lowest vibrational levels. In a further study [20] (hereafter referred to as paper II), we presented similar data for rotational transitions in collisions of 4 HeH + with electrons.…”
Section: Introductionmentioning
confidence: 99%
“…Our improved channel elimination procedure removes this ambiguity to evaluate accurate results at low energy (<0.01 eV). This and our previous study [33] make us believe that once the collisional excitation cross section data is available, the analysis of the intensities of infra-red and microwave regions can provide information for the diagnostics of tokamak, as well as the study of planetary atmospheres and of the interstellar medium.…”
Section: Discussionmentioning
confidence: 56%
“…Due to the general 1/E el -dependence of cross sections σ j ←j , the calculated rate coefficients behave as 1/ √ T for de-excitation and exp −∆ j j /T / √ T for excitation transitions, where ∆ j j = E j µ − E jµ (with µ = µ = 0 for the present case) is the excitation energy. Therefore, similarly to References [16,33], for convenience of use, the rate coefficients are fitted to the formula…”
Section: Cross Sections and Rate Coefficientsmentioning
confidence: 99%
“…In practice, 55,86,87 if one uses the UK R-matrices codes, 17 the scattering matrix should be obtained from the reactance matrix…”
Section: Polyatomic Moleculesmentioning
confidence: 99%